The dependence between European Union carbon market and crude oil market: A copula analysis. Issue 4 (February 2019) - Du, Ziping; Feng, Mianmian
Abstract: The current literature analyzed the dependence between EU carbon market and the crude oil market from the perspectives of linear regression and Granger causality test. In this paper, we examine the dependence between carbon market and crude oil market using a particular class of copula model. By using different constant copula models, our findings suggest that the dependence between the two markets is symmetric, and the dependence structure has changed during different phases. Meanwhile, the dependence in the third phase is weaker than the dependence in the second phase. By analyzing the time-varying copula, we come to the conclusion that the time-varying dependence coefficient fluctuates greatly, and there is greater dependence in the period of crisis and instability.